26a - Evans, Diana (Vintage Books, 2006)
In the attic room at 26 Waifer Avenue, identical twins Georgia and Bessi Hunter share nectarines and forge their identities, while escaping from the sadness and danger that inhabit the floors below. But innocence lasts for only so long$1 (Band dreams, no matter how vivid and powerful, cannot slow the relentless incursion of the real world.s
Keywords: Fiction